Laproscopic evaluation in primary female infertility - Bhatia, Ruby; Kaur, Paramjit; Kaur, Gurpinder; Mor, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is defined as inability to conceive within one or more years of regular unprotected coitus. Infertility has now a days not only a medical but a social problem as well. Ignorance and illiteracy, coupled with hesitancy to discuss the problem, complicates the matter further. WHO has listed infertility as a global health issue. Methods: The present study was conducted on 64 patients with female factor primary infertility admitted in department of obstetrics and gynecology at Rajendra Hospital, Patiala over a duration of 1 year (December 2013- November 2014). All the patients had normal semen study of their partner. Results: In our study mean age was 27.87±4.57. No patient was above 40 years of age. Duration of infertility between 1-5 years was in 47 patients (73.43%), nine patients (14.06%) were infertile for 6-10 years. Out of 64 patients of primary infertility, majority of patients were of endometriosis 15(23.43%), followed by pelvic inflammatory disease 14(21.87%), tubal blockade in 7(10.9%), PCOD in 6(9.37%). 14.08% patients had normal laproscopic study. 34 patients (53.12%) had bilateral spill while no spill was seen in 12 patients (18.75%). Unilateral spill was seen in seven patients (10.93%) while six patients (9.37%) had delayed spill. Conclusions: Prevalence of infertility is increasing, so is the awareness and treatment seeking behavior. The present study assures that in evaluation and workup of primary infertility patients, after baseline noninvasive investigations, endometrial sampling and HSG, the diagnostic and operative laproscopy is an excellent tool for evaluation of tubal factor. Least expected conditions like endometriosis on clinical evaluation, can be diagnosed and treated with ease on laproscopy. Although tubal factor has been considered to be responsible for a large percentage of cases with female secondary infertility since decades, but in present study laproscopic evaluation confirmed tubal factor in 85.01% cases with female factor infertility.